Analisis Indeks Desa Membangun untuk Mengetahui Pola Perkembangan Pembangunan Desa di Kecamatan Gadingrejo Kabupaten Pringsewu - Muhtarom STIT; Nurhadi Kusuma; Eri Purwanti (Balitbangda Provinsi Lampung, 2018)
Village development Index is an index used to determine of rural development by using indicators of Social Security Index (IKS), Economic Resilience Index (IKE), and Environmental Resilience Index (IKL). The purpose of this study is to determine the pattern of development of village development in the social, economic, and environmental fields. This research uses descriptive Quantitative approach. Analysis this study using triangulation data analysis. The results showed that the majority of villages in Gadingrejo sub-district belong to the Classification of Developing Villages of 87%. The Social Security Index score is the highest indicator in the realization of village development in Gadingrejo sub-district, which is 0.71. This shows the average of villages in the sub-district of gadingrejo social resilience / social development is in advanced calcification. The village community empowerment activities in Gadingrejo are able to contribute positively in promoting social resilience.